UKRAINE ІN THE CONTEXT OF CURRENT GLOBAL PROBLEM - Avksentiev, Oleksandr; Baleja, Piotr (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2026)
The current Ukrainian situation is analyzed through the prism of the hierarchy of global world problems that emerged after World War II. The global trends in the process of forming a new model of the world order are characterized, which have a decisive impact on changing international relations and interstate regulation. The signs of the reverse trend - deglobalization, and its manifestations in European countries are described. The Russian-Ukrainian war is considered as a factor of geopolitical shifts and the destruction of the international security system. The interconnectedness of the intensification of interstate competition and the intensification of the struggle for one’s own geopolitical interests using various means is emphasized. The danger to the regional balance of power in Europe is indicated due to the presence of buffer zones on the territory of Ukraine - the self-proclaimed DPR and LPR. The possible consequences of Russia’s recognition and support of quasi-states as a factor of the further unregulated spread of the emergence of such entities and the destruction of the system of international relations and security are expressed. It is noted that the beginning of Russia’s full-scale war against Ukraine has put on the agenda the formation of a new European security system, of which Ukraine should become a part, and the issue of a system of international control over nuclear weapons. The negative consequences of the war against Ukraine, starting in 2014, for Russia itself, which were realized during the first years of the war, are indicated. Relations with Poland since the Russian-Ukrainian war are considered as a positive example of humanitarian assistance and laying the foundations for future cooperation. The issue of the growing danger of a migration wave in Europe is separately considered, which should serve as a warning for Ukraine against inviting a significant number of migrants with a different mentality as workers in various sectors of the Ukrainian economy. The need to pay important attention in the post-war period to create favorable conditions for the restoration of the middle class in the country is indicated, the importance of which is proven by the experience of Europe. Whatever epithets have been given to Ukraine – «Heart of Europe», «gateway to Europe», «buffer zone», «country of strategic transit», «civilizational crossroads», «divided country» – and all these are just fragments of the unwritten history of Ukraine, since this history is still being written by its people.